Effects of illusory kinesthesia by tendon vibratory stimulation on the postoperative neural activities of distal radius fracture patients. Issue 17 (6th December 2017) - Imai, Ryota; Osumi, Michihiro; Ishigaki, Tomoya; Kodama, Takayuki; Shimada, Sotaro; Morioka, Shu
Abstract : Activation of motor-related regions with illusory kinesthesia had been suspected to contribute toward pain alleviation. We used electroencephalography (EEG) to assess the sensorimotor cortex activation during illusory kinesthesia by vibratory tendon stimulation in patients who were in pain. We investigated the relationship between the sensorimotor cortex and postoperative pain to clarify the analgesia mechanism. Patients who had undergone distal radius fracture surgery were studied. A hand massager provided the vibration stimulus for the illusory kinesthesia on the extensor digitorum muscle at the nonaffected hand's wrist joint on 7 consecutive days starting 1 day after surgery. The main outcomes were pain intensity and EEG activity. EEG activity was recorded during illusory kinesthesia. We also analyzed the high α rhythm (10–12 Hz) event-related desynchronization/event-related synchronization. The pain intensity was reduced. Attenuation of the high α wave was observed in the bilateral sensorimotor cortex (C3ch, C4ch) areas during illusory kinesthesia. A significant negative correlation was also observed in the C3 and the C4 of event-related desynchronization/event-related synchronization% values and the variation of pain amelioration at rest. Activation of the sensorimotor cortex by illusory kinesthesia might have influenced parts of the descending pain-inhibitory system. The postoperative pain in the patients might have been alleviated by the descending pain-inhibitory system.